ADAPTASI UMAT HINDU DI KOTA PEKANBARU - Rama Fauzi; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in the Agung Jagatnatha Temple of Pekanbaru. The purpose of this research was to analyze how the presence of Hindu’s and lived in Pekanbaru with describe the social practices of the theory of habitus, capital, and arena based on Bourdieu's theory, as well as adaptation to the existence in developing religious social activities to live a life that is lived in urban areas such as in the city of Pekanbaru. The subject in this study consist of seven people. The subject of this research is where Hindu’s who actively come and influential religious social activities in following in Agung Jagatnatha Temple with long settled in Pekanbaru. Sampling is done by accidental sampling techniques. Instrument data are observation, interview, and documentation. The author uses descriptive qualitative methods with data analysis refers to the concept of Milles & Huberman consists of data collection, data presentation, reduction of data and withdrawal of the conclusion. The results showed that capital used by Hindu’s in Pekanbaru in the presence of social capital in the form of solidarity, confidence, attitude of tolerance, social interaction and network proximity between interesting people, as well as the forms of participation that done Hindu’s, while more cultural capital to social religious activities, the implementation of religious ceremonies, the application of capital of culture on children and between Hindu’s, as well as the expectations of Hindu’s in developing implementation. Capital economics, the Dharma Karya cooperation, Suka Duke gathering, fundraising, as well as more symbolic capital to social roles owned by Hindu’s against Temple surroundings. As for the strategy of Hindu’s in developing social activities of religious existence in Pekanbaru shows that there is a biological strategy, investment strategy, successive strategy educational and economic strategy. Adaptation of Hindu’s society in Pekanbaru was included in the minority with capital obtained comes from the Hindu community of its own, such as the PHDI (Parisadha Hindu Dharma Indonesia) as well as the WHDI (Wanita Hindu Dharma Indonesia) by having a religious ceremony hereditary that should be conserved.Keywords : Adaptation, Hindu’s, Capital, Strategy